(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2019)
Law No. 13.344, of October 6, 2016, came into force in Brazil to much applause from the national legal community and, in particular, from professionals working in the conflictive and delicate area of human trafficking. Celebrated by the press as a legislative milestone, the text originated in a project by the Parliamentary Commission of Inquiry (CPI) into National and International Human Trafficking in Brazil, which worked in the Senate between 2011 and 2012 (PL No. 7.370/2014). In fact, it was long overdue for Brazil’s domestic legislation on combating human trafficking to adapt to the Additional Protocol to the Palermo Convention, ratified by Brazil and in force in the country since March 12, 2004.1 The new law, enacted in this spirit, focused on the three central lines of action of the aforementioned international law, namely: prevention, repression and assistance to victims. Translated with DeepL.com (free version)